Training of specialists in the field of physical culture and sports in Poland - Matuzna, Anastasiia; Arabadzhy, Anna (Національний технічний університет "Харківський політехнічний інститут", 2025)
The thesis examines the specifics of training specialists in the field of physical culture and sports in Poland, using the example of education in Institutes of Physical Culture (Academy of Physical Education in Warsaw). The structure of educational programs, their compliance with European standards, teaching methods, and practical training of students are analyzed. The main differences between the Polish system of specialist training and similar programs in other countries are identified.
Keywords: physical culture; sports; specialist training; education; Poland